Diversity of Yeasts and Molds by Culture-Dependent and Culture-Independent Methods for Mycobiome Surveillance of Traditionally Prepared Dried Starters for the Production of Indian Alcoholic Beverages - Sha, Shankar Prasad; Suryavanshi, Mangesh Vasant; Jani, Kunal; Sharma, Avinash; Shouche, Yogesh; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2018)
Marcha, thiat, dawdim, hamei, humao, khekhrii, chowan and phut are traditionally prepared amylolytic starters use for production of various ethnic alcoholic beverages in North East states in India. The surveillance of mycobiome associated with amylolytic starters from North East states of India have been revealed by using phenotypic and molecular tools. We identified Wickerhamomyces anomalus, Pichia anomala, Saccharomycopsis fibuligera, Pichia terricola, Pichia kudriavzevii, and Candida glabrata by ITS-PCR. The diversity of yeasts and molds in all forty samples was also investigated by PCR-DGGE. The average distributions of yeasts showed Saccharomyces cerevisiae (16.5%), Saccharomycopsis fibuligera (15.3%), Wickerhamomyces anomalus(11.3%), Sm. malanga (11.7%), Kluyveromyces marxianus(5.3%), Meyerozyma sp. (2.7%), Candida glabrata (2.7%), Saccharomyces sp. (1.3%), Hyphopichiaburtonii(1.2%), Schwanniomyces occidentalis (1.1%), Pichia kudriavzevi (1.0%), Torulaspora delbrueckii (1.0%), Zygosaccharomyce sbailii (1.0%), P. guilliermondii (1.0%), C. Parapsilosis (0.4%), Komagataella pastoris (0.3%), Saccharomycopsis capsularis (0.6%), S.paradoxus(0.6%), and C. tropicalis (0.1%). Average distributions of molds were Aspergillus penicillioides (5.0%), Rhizopusoryzae (3.3%), sub-phyllum: Mucoromycotina (2.1%), Cryptococcus amylolentus (1.7%), Xerochrysium dermatitidis (1.6%), A. oryzae (1.3%), Neosartorya fischeri (0.8%), A. proliferans (0.6%), Chrysozymagrise oflava (0.6%), Stilbocreasp. (0.6%), Mucor circinelloides (0.5%), and Aureobasidium pullulans (0.4%).